At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
Hoot! You just asked your first question! Hang tight while I find people to answer it for you. You can thank people who give you good answers by clicking the 'Good Answer' button on the right!
In order to find the x intersection, you have to set y=0 in the equation. In the same way to find the y-intercection, make x=0, that is: x-inter: 3x+2(0)=6 x=2 Answer 1 y-inter: 3(0)+2y=6 y=3 Answer 2
Feed in values of x so that y = 0 then do the same for values of y so tht x = 0 You will have two coordinate points and you then join a line through them. Let x =0 then y = 3 Let y = 0 then x = 2 This gives the coordinates (0, 3)and (2, 0)
Thank you so much I really appreciate it. Excellent job!!
Do I do this problem the same way? y=x-2
yeah exactly the same way. This method works for any linear equation.
okay I think I got it enjoy your day
3x+2y=6 To find the x-intercept, substitute in 0 for y and solve for x. 3x+2(0)=6 Multiply 2 by each term inside the parentheses. 3x+0=6 Remove the 0 from the polynomial; adding or subtracting 0 does not change the value of the expression. 3x=6 Divide each term in the equation by 3. (3x)/(3)=(6)/(3) Simplify the left-hand side of the equation by canceling the common factors. x=(6)/(3) Simplify the right-hand side of the equation by simplifying each term. x=2 To find the y-intercept, substitute in 0 for x and solve for y. 3(0)+2y=6 Multiply 3 by each term inside the parentheses. 0+2y=6 Combine all similar expressions. 2y=6 Divide each term in the equation by 2. (2y)/(2)=(6)/(2) Simplify the left-hand side of the equation by canceling the common factors. y=(6)/(2) Solve the equation. y=3 These are the x and y intercepts of the equation 3x+2y=6. x=2, y=3